Protective role of resilience on COVID-19 impact on the quality of life of nursing students in the Philippines - Jean Nunez Guillasper; Ryan Michael Flores Oducado; Gil Platon Soriano (Belitung Nursing Journal, 2021)
Background: Studies have shown that resilience has a buffering effect on mental health problems. However, the influence of resilience on the impact on the Quality of Life (QoL) in the context of the COVID-19 pandemic has not been well documented. Objective: This study examined the influence of resilience on the COVID-19 impact on QoL among nursing students. Methods: A cross-sectional research design was utilized. Three hundred and forty-five students of a government-funded nursing school in the Philippines responded in the web-based survey. Data were gathered using two adopted instruments from 18 to 31 August 2020. Test for differences and correlational analyses were performed. Results: The COVID-19 pandemic had a moderate impact on the QoL of nursing students. The COVID-19 impact on QoL significantly varied with sex and the nearby presence of COVID-19 cases. Bivariate analysis revealed a significant moderate inverse relationship between psychological resilience and the impact of COVID-19 on QoL. Conclusion: Resilience has a protective influence on the impact on QoL concerning main areas of mental health in the context of the COVID-19 pandemic. Understanding the factors and developing interventions that build the resilience of students is a focal point of action for nursing schools.